Parler de l’intimité avec ses langues - Corinne Mencé-Caster (Catalonia)
This article proposes to reflect on the category of intimacy in language studies, by focusing on "diglotte" speakers and the singularity of their speech. By producing utterances that are the result of the articulation of at least two languages, these speakers question the notion of "system where everything fits together" and tend to demonstrate the relevance of the notion of "poly-system". Taking this poly-system into account reveals the need for a linguistic hermeneutic coupled with a pragmatics that questions the concept of "grammaticality", so as not to construct an exclusive and excluding norm. It is at this price that the linguistic intimacy of the 'diglottes' speakers can be unearthed and that they can escape the feeling of shame that constantly threatens them.